How to meet patients' individual needs for drug information - a scoping review - Kusch, Marcel; Haefeli, Walter E.; Seidling, Hanna (Patient preference and adherence, 2018)
Purpose: The aim of this study was to 1) describe drug information desired by patients and 2) analyze how such information could be customized to be presented to patients according to their individual information needs. Materials and methods: We performed a scoping literature search and identified relevant drug information topics by assessing and clustering 1) studies analyzing patients’ enquiries to drug information hotlines and services, and 2) qualitative studies evaluating patient drug information needs. For the two most frequently mentioned topics, we further analyzed which components (ie, information domains) the topics contained and examined patients’ and health care professionals’ (HCPs) views on these components. Results: Of 27 identified drug information topics in the literature search, patients most frequently requested information on adverse drug reactions (ADRs) and drug-drug interactions (DDIs). Hypothetically, those topics are composed of seven distinct information domains each (eg, ADR and DDI classification by frequency, severity, or onset; information on management strategies, monitoring, and prevention strategies). Patients’ and HCPs’ appraisal concerning the information content of these domains varies greatly and is even lacking sometimes.Conclusion: Patients particularly request information on ADRs and DDIs. Approaches to customize such information are sparse. The identified information domains of each topic could be used to structure corresponding drug information and to thus facilitate customization to individual information needs. Keywords: medication information, information needs, customization, adverse drug reactions, side effects, drug-drug interactions